Case report: Rubella virus-induced cutaneous granulomas in a girl with atypical SCID caused by DCLRE1C gene mutations - Deng, Sihan; Rao, Shijia; Wang, Alun R.; Shi, Wei (Frontiers in Genetics, 2023)
Here we report a case of rubella virus-induced granulomatous dermatitis in a young girl with immunodeficiency caused by DCLRE1C gene mutations. The patient was a 6-year-old girl who presented with multiple erythematous plaques on the face and limbs. Biopsies of the lesions revealed tuberculoid necrotizing granulomas. No pathogens could be identified on extensive special stains, tissue cultures, or PCR based microbiology assays. Metagenomic next-generation sequencing analysis revealed rubella virus. Underlying atypical severe combined immunodeficiency was recognized for the patient, based upon patient’s history of repetitive infections since birth, low T-cell, B-cell, and NK cell counts, and abnormal immunoglobulins and complements. To reveal the genetic abnormality of the atypical SCID, a whole-exome sequencing was performed and compound heterozygous mutations of DCLRE1C gene were detected. This report highlights the diagnostic values of metagenomic next-generation sequencing in identifying rare pathogens causing cutaneous granulomas in patients with atypical SCID.